1998
DOI: 10.1002/(sici)1097-4652(199801)174:1<9::aid-jcp2>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor (EGF) receptor density controls mitogenic activation of normal rat kidney (NRK) cells by EGF

Abstract: Normal rat kidney (NRK) fibroblasts are immortalized cells that are strictly dependent on externally added growth factors for proliferation. When cultured in the presence of epidermal growth factor (EGF) as the only growth stimulating hormone, these cells have a normal phenotype and undergo density-dependent growth inhibition. It has been postulated that this density-arrest results from a decrease of EGF receptor levels below a threshold level which makes these cells unresponsive to stimulation by EGF. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Previous studies have shown that the mitogenic effect of EGF correlates with EGFR density [49]. The contrast in EGFR expression between the PCK rat and human ARPKD or murine models of human ARPKD remains unexplained.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies have shown that the mitogenic effect of EGF correlates with EGFR density [49]. The contrast in EGFR expression between the PCK rat and human ARPKD or murine models of human ARPKD remains unexplained.…”
Section: Discussionsupporting
confidence: 59%
“…Normal rat kidney (NRK) fibroblasts have been used widely as an in vitro model system for studying the mechanisms of density-dependent growth regulation and oncogenic cell transformation [25,26,50]. Previous studies have shown that the arachidonic acid metabolite prostaglandin F2a (PGF2a), which activates the Fprostanoid (FP)-subtype of prostanoid receptor [35], induces phosphoinositide turnover in NRK fibroblasts thereby increasing the intracellular calcium concentration in these cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…Optimal cycle numbers were determined as described [23]. Under these conditions competitive interference was absent and twofold changes in the abundance of PCR products were detected over a span of 4–5 cycles, making this method suitable to monitor EGF receptor mRNA expression [14].…”
Section: Methodsmentioning
confidence: 99%
“…When cultured in the presence of epidermal growth factor (EGF) as the only growth stimulating hormone, these immortalized cells have a normal phenotype and undergo DDGI. In the additional presence of modulating factors such as retinoic acid (RA) or transforming growth factor β (TGF‐β), which by themselves are not mitogenic for these cells, density arrested NRK cells become responsive again to the growth stimulatory effect of EGF, resulting in loss of DDGI [12–15]. It has been established that the number of EGF receptors in NRK cells decreases with increasing cell density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation